Taxpayer Compliance In Paying Land And Building Tax In Karang Berombak Village West Medan - Khairani Agustin; Dinda Lutfiah; Sheila Nur Aulia; Galih Supraja (Yayasan Multidimensi Kreatif, 2024)
Public compliance in paying land and building tax obligations in Karang Berombak Village, West Medan still has not provided an increase in land and building tax payments. The compliance of the taxpayer community is very important in determining the land and building tax that has been designed by the government. This research aims to find out what are the causes of taxpayer non-compliance in paying land and building tax in Karang Berombak Village, West Medan. This research uses a qualitative descriptive method. The data collected came from observations at the research location, interviews with one of the UPT IV staff of the Medan City Regional Revenue Agency, and documentation related to the research. The results of this study as well as some information provided by informants showed that the low compliance of taxpayers in Karang Berombak Village, West Medan was triggered by economic factors, lack of socialization regarding land and building tax, outdated data, tax subjects who do not occupy tax objects, public dissatisfaction with public services, and technical constraints on the digital payment system.